Replacing Dietary Fish Meal with Defatted Black Soldier Fly (Hermetia illucens) Larvae Meal Affected Growth, Digestive Physiology and Muscle Quality of Tongue Sole (Cynoglossus semilaevis) - Li, Xueting; Qin, Chuanjie; Fang, Zhenzhen; Sun, Xueliang; Shi, Hongyue; Wang, Qingkui; Zhao, Honghao (Frontiers in Physiology, 2022)
For solving the global shortage of fish meal (FM) supplies from fisheries, the black soldier fly (Hermetia illucens) has become a new protein alternative in aquatic feeds. The present study investigated the effects of dietary inclusion of defatted H. illucens larvae meal (DBLM) on growth, serum biochemical parameters, digestive function, and muscle quality of tongue sole (Cynoglossus semilaevis). The feeding experiment consisted of five experimental diets: a control diet based on FM protein (H0) and four DBLM diets, substituting 25% (H25), 50% (H50), 75% (H75), and 100% (H100) of FM. C. semilaevis (initial weight 563.48 ± 22.81 g) were randomly allocated over five treatments in quadruplicate. After 65 days of feeding, the weight gain rate (WGR), specific growth rate (SGR), and protein efficiency ratio (PER) were significantly higher in H0 and H25 groups with less feed conversion ratio (FCR) and feed intake (FI). The concentrations of serum ALT, TG, T-CHO, ALB, and GLO and their ratio (i.e., A/G) in the H25 group were also significantly higher than those in the other DBLM diet-feeding groups. The digestive enzyme activities first increased (from 25% to 75%) and then decreased (from 75%) with the increased level of DBLM in diets. Meanwhile, there were significant improvements in the thickness of the intestinal longitudinal muscle (LM), circular muscle (CM), columnar epithelium (CE), and lamina propria (LP) in H25 C. semilaevis compared to the control group (p < 0.05). The fish from the other DBLM diets groups presented significant reductions in the thicknesses of LM, CM, CE, and LP, as well as the length of microvilli (ML) in a dose-dependent manner (p < 0.05). However, the substitution of FM increased up to 50% would result in intestinal structural damage. Moreover, the proximate compositions, antioxidant and water holding capacity, and muscular structures of C. semilaevis fillets were all significantly affected after substituting 25% FM with DBLM (p < 0.05). Except for the dry matter, moisture, ash, crude fat, and protein contents were significantly higher in H25 C. semilaevis muscles. The SOD activity in the H0 group was significantly lower than that in the H25 group. The CAT activity in C. semilaevis muscles prominently reduced along with the increase in DBLM content in feeding diets (p < 0.05). The water holding capacity of C. semilaevis fillets was best in the H25 group. In summary, the optimum proportion of DBLM with FM for feeding C. semilaevis may be around 25%.